Improving Science Learning Outcomes through the Snowball Throwing Strategy for Fifth Grade Students at SDN 2 Ngargosari - Ariyani Wahyuningsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to improve student learning outcomes through the application of the Snowball Throwing strategy in fifth grade science learning at SDN 2 Ngargosari. This research is a Classroom Action Research conducted in 2 cycles. The research subjects were teachers of class V and students of class V, totaling 17 students. Data collection methods are carried out by observation, tests, interviews and documentation. Data analysis techniques use the stages of data reduction, data presentation, and data verification or drawing conclusions. The results showed that there was an increase in student learning outcomes in science learning at the end of cycle II reaching 88.24%, which before taking action the percentage was 35.29%. This study concludes that the snowball throwing strategy can improve student learning outcomes in grade V science subjects.